Analisis Kebutuhan Alat Muat dan Alat Angkut untuk Perubahan Shift Kerja pada Quarry Batugamping PT X, Jawa Barat: Analysis of Loading and Hauling Equipment Requirements for a Shift Work Change at a Limestone Quarry PT X, West Java - Seprizal, Muhammad Faisal; Yanottama, Andy; Permadi, Dimas Agung; Navtalia, Zella; Agustine, Diah Wully (MINERAL, 2025)
PT X is a company engaged in the limestone mining sector and simultaneously serves as a cement supplier. The company plans to transition from a three-shift work schedule to a two-shift system. This decision is driven by the increasing costs associated with mining, safety concerns, and time losses due to equipment maintenance, following various evaluations conducted by the company's management. This research aims to analyze the requirements for loading and transportation equipment necessary to achieve an annual production target of 4,500,000 tons after the implementation of the two-shift work schedule. The research methodology employed is quantitative, encompassing the collection of both primary and secondary data, as well as an analysis of equipment productivity. The findings indicate that to maintain the production target, it is essential to replace the current loading equipment from the CAT 988B wheel loader to the CAT 990H wheel loader. Additionally, adjustments to the number of equipment are required, including two units of the CAT 990H wheel loader and seven units of the CAT 773 dump truck for Crusher 1, as well as two units of the CAT 992K wheel loader and eight units of the CAT 777D dump truck for Crusher 2. The production capacity of this equipment configuration reaches 4,575,457 tons per year, demonstrating that the production target can be optimally met despite the reduction in the number of work shifts.